2019
DOI: 10.1002/prs.12109
|View full text |Cite
|
Sign up to set email alerts
|

Fire behaviors of vertical and horizontal polymethyl methacrylate slabs under autoignition conditions

Abstract: In this study, horizontal and vertical black polymethyl methacrylate (PMMA) samples were investigated experimentally and theoretically under 25‐70 kW/m2 heat flux with autoignition conditions. An empirical model was developed to predict the autoignition time, where the significance of this model is to unify the prediction for both horizontal and vertical samples. Both horizontal and vertical samples show similar phenomena, such as burning stages and no higher than 2 cm sample expansion. It is obtained that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…A comparison between measured and predicted t ig , T sig, and m sig in the range of heat fluxes 25-150 kW/m 2 is also carried out for the spontaneous ignition in Figures 10-12, respectively. As most of the measurements [23,25,28,52,[55][56][57][58] refer to clear PMMA, simulations have been carried out for clear LMW and HMW PMMA with thermal and thermo-oxidative kinetics, but results for black LMW and HMW PMMA with thermo-oxidative kinetics are also included for comparison. As expected, it can be observed that the best agreement between predicted and measured t ig is obtained with the data of clear LMW PMMA with thermo-oxidative kinetics.…”
Section: Comparison Between Predictions and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison between measured and predicted t ig , T sig, and m sig in the range of heat fluxes 25-150 kW/m 2 is also carried out for the spontaneous ignition in Figures 10-12, respectively. As most of the measurements [23,25,28,52,[55][56][57][58] refer to clear PMMA, simulations have been carried out for clear LMW and HMW PMMA with thermal and thermo-oxidative kinetics, but results for black LMW and HMW PMMA with thermo-oxidative kinetics are also included for comparison. As expected, it can be observed that the best agreement between predicted and measured t ig is obtained with the data of clear LMW PMMA with thermo-oxidative kinetics.…”
Section: Comparison Between Predictions and Measurementsmentioning
confidence: 99%
“…The inverse of the square root of the spontaneous ignition delay time as a function of the heat flux, Q, as predicted for clear and black LMW (solid and dotted blue lines) and HMW (solid and dotted brown lines) PMMA with thermo-oxidative decomposition kinetics and for clear LMW (dashed blue line) and HMW (dashed brown line) PMMA with purely thermal decomposition kinetics.Experimental data (symbols) derived from the literature are also reported. (See Refs [25,28,[55][56][57][58]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…cross-laminated timber 10 ) The determination of the thermal properties for timber is much more challenging than those isotropic construction materials, such as steel, 11 concrete 12 and polymers. 13 For example, as an anisotropic material, timber’s thermal conductivity to the fibre orientation is generally twice of that perpendicular to fibre. 14 Some of its characteristics even complicate the situation, such as internal moisture 15 and pyrolysis behaviours under a high-temperature environment.…”
Section: Introductionmentioning
confidence: 99%